A unified model to manage requirement engineering for global software development - ALQarni, Turki A.; Noor Muhammad, Rizwan Jameel (Kuwait Journal of Science, 2019)
Change is an unavoidable activity during software development. Requirements can be changed due to many reasons like the demands of customers, organizational needs and scalability. It is crucial to manage these changes on time to achieve successful software. However, requirement change management (RCM) is not a straightforward activity especially in case of global software development (GSD) due to distributed team structure and geographical challenges. Moreover, no collocated RCM model or organizational structure is currently available to do GSD. This paper proposes a novel unified model to manage requirement engineering for GSD. The research is validated using a survey. The results are found encouraging and it is anticipated that the proposed research will help software companies to solve the changing requirements problems in GSD environment to complete projects successfully.